Surface Functionalized Barium Titanate Nanoparticles: A Combined Experimental and Computational Study. (1st June 2022) - Domrzalski, Jessica N.; Stevens, Tyler E.; Van Ginhoven, Renee M.; Fritzsching, Keith J.; Walder, Brennan J.; Johnson, Emily M.; Lewis, Riley E.; Vreeland, Erika C.; Pearce, Charles J.; Vargas, David A.; Coker, Eric N.; Martinez, Estevan J.; et al.
Abstract : Barium titanate (BTO) nanoparticles show great potential for use in electrostatic capacitors with high energy density. This includes both polymer composite and sintered capacitors. However, questions about the nanoparticles' size distribution, amount of agglomeration, and surface ligand effect on performance properties remain. Reducing particle agglomeration is a crucial step to understanding the properties of nanoscale particles, as agglomeration has significant effects on the composite dielectric constant. BTO surface functionalization using phosphonic acids is known reduce BTO nanoparticle agglomeration. We explore solution synthesized 10 nm BTO particles with tert -butylphosphonic acid ligands. Recent methods to quantifying agglomeration using an epoxy matrix before imaging shows that tert -butylphosphonic acid ligands reduce BTO agglomeration by 33%. Thermometric, spectroscopic, and computational methods provide confirmation of ligand binding and provide evidence of multiple ligand binding modes on the BTO particle surface.